Investigating the Behavior of Concrete and Mortar Reinforced with Aluminum Waste Strips - Shakir Muwashee, Rawa; Athab Al-Jameel, Hamid; Abdulhameed Jabai, Qusay (International Journal of Engineering and Technology, 2018)
Composite  concrete such as fiber reinforced concrete is widely used in structures because of its excellent properties such as compressive, flexural and tensile strengths and also high modulus of elasticity because it gives lower strain values under loading and too fewer cracks propagation. In this study, Aluminum strips was prepared by cutting the Coca- Cola cans as strips in concrete. The reason of using Aluminum strip is low density and good tensile strength (about 310 MPa) and also has a good ductility.  The results of this study show good improvements in compressive, tensile and  flexural strengths using 117 tested specimens for both concrete and mortar. In brief, about 22 % increment in compressive strength of Aluminum strip concrete  and flexural strength increases from 3.31 MPa to 11.20 MPa when using Aluminum strips with 2.5 % by volume of concrete. The reinforced mortar with Aluminum strips demonstrates significant increments which are 27% for compressive strength and more than 100% for both flexural and tensile strengths comparing with reference mix.